(untitled) (Anclajes, 2024)
The poetic works of Juan L. Ortiz, Francisco Madariaga, Martín Rodríguez and Javier Cófreces and Alberto Muñoz imagine an amphibian origin between childhood and language, between timeless myth and historical-political time, between the subjective and the impersonal, between nature and culture. Assuming a method of reading that is also amphibious (oscillating among the symbolic, phenomenological, psychoanalytic and political-aesthetic), we intend to explore the ways in which each of these works imagines, in a singular way, the space and time of origin as poetry, that is, making the word and the object coincide